Effects of Time Constraints and Goal Setting on Basketball Shooting - Kostrna, Jason (Frontiers in Psychology, 2022)
In sport, numerous high-pressure situations require athletes to perform motor tasks under temporally-constrained circumstances. The present study investigated the effects of time constraints on anxiety, attention, performance, and mechanics of basketball free-throw shooting. Additionally, the potential benefits of goal setting were examined in relation to performance in time-constrained situations. Forty undergraduates (n = 10 elite basketball players, n = 15 experienced, n = 15 inexperienced) shot free throws in timed, untimed, and goal-oriented conditions. In the timed condition, participants attempted to make as many shots as possible in 30 seconds. In the untimed condition, participants took the same number of shots as they did in the timed trial but without a time constraint. In the goal-oriented condition, participants attempted to surpass their highest number of made shots while once again under a 30-second time constraint. Participants in the timed condition had the worst shooting accuracy (M = 45.20%, SD = 21.96%), while the untimed (M = 55.76%, SD = 21.12%) and goal-oriented conditions (M = 55.79%, SD = 22.92%) had similar shooting percentages. In addition, joint consistency in the elbow and knee increased during the untimed condition compared to both timed and goal-oriented conditions. Results indicate that a goal-oriented focus may prevent performance declines present in time-constrained situations.